2005
DOI: 10.1111/j.1461-0248.2005.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of non‐limiting substrates to increase size; a generic strategy to simultaneously optimize uptake and minimize predation in pelagic osmotrophs?

Abstract: Coexistence of two organisms competing for the same nutrient is possible if one is an ÔuptakeÕ, and the other a Ôpredation defenceÕ specialist. In pelagic food webs this principle has been linked to cell size. Small osmotroph cells, with their high surface : volume ratio, have been argued to be uptake specialists, while larger osmotrophs avoiding the intense grazing pressure from small protozoan predators might represent Ôpredation defenceÕ specialists. This may seem like an obligatory trade-off situation that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
180
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(190 citation statements)
references
References 59 publications
7
180
0
Order By: Relevance
“…In general, larger cell size is a predator avoidance strategy because of limitations of prey handling capabilities, whereas smaller cells should be superior in nutrient uptake rates because cell size determines the rate of diffusive nutrient transport (Thingstad et al, 2005). We found a negative relationship between cell size and diversity ( Figure 3c) and community composition ( Table 1).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In general, larger cell size is a predator avoidance strategy because of limitations of prey handling capabilities, whereas smaller cells should be superior in nutrient uptake rates because cell size determines the rate of diffusive nutrient transport (Thingstad et al, 2005). We found a negative relationship between cell size and diversity ( Figure 3c) and community composition ( Table 1).…”
Section: Discussionmentioning
confidence: 59%
“…Unicellular organism size is known to be a very plastic trait; on the one hand, size is believed to play an important role for the uptake of dissolved substrates and, on the other hand, to be strongly influenced by predation (Thingstad et al, 2005;Jiang, 2007). In general, larger cell size is a predator avoidance strategy because of limitations of prey handling capabilities, whereas smaller cells should be superior in nutrient uptake rates because cell size determines the rate of diffusive nutrient transport (Thingstad et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a number of structural and biophysical features of large phytoplankton may counterbalance their geometric constraints on resources acquisition, which otherwise favour small cells when resources are limiting [45,48]. These traits include the possession of intracellular vacuoles to increase nutrient storage capacity [47,49], changes in cell shape [50,51], the use of non-limiting substrates to increase cell size without increasing nutrient requirements [52], the ability to migrate vertically in the water column [53] and the establishment of associations with nitrogen fixers [54].…”
Section: Discussionmentioning
confidence: 99%
“…In a twist on this perspective, Thingstad argued that bacterioplankton may increase their cell size to succeed by defense specialism--growing too large for their predators. He theorized that the surface-to-volume ratio is less important than the surface-to-'cell requirements of a limiting element', and that larger cells can maintain the benefits of smaller cells by scaling up their cell composition by accumulating non-limiting nutrients such as carbon in an N-and P-limited system (Thingstad et al, 2005). The theory that selection favors small genomes because they can be replicated more rapidly, thus shortening generation times, has largely been ruled out by studies that found no correlation between generation time and genome size (Mira et al, 2001;Lynch, 2006;Touchon and Rocha, 2007;.…”
Section: Streamlining Theorymentioning
confidence: 99%